Does altered mandibular position and dental occlusion influence upper cervical movement: A cross-sectional study in asymptomatic people - Grondin, F.; Hall, Toby; von Piekartz, H. (Churchill Livingstone, 2017)
Objective: Gross mandibular position and masticatory muscle activity have been shown to influence cervical muscles electromyographic activity. The purpose of this study was to investigate the influence of three different mandible positions including conscious occlusion, tongue tip against the anterior hard palate (Palate tongue position) and natural resting position (Rest), on sagittal plane cervical spine range of motion (ROM) as well as the flexion-rotation test (FRT) in asymptomatic subjects. Materials and methods: An experienced single blinded examiner evaluated ROM using an Iphone in 22 subjects (7 females; mean age of 29.91years, SD 5.44). Results: Intra-rater reliability for range recorded was good for the FRT with ICC (intraclass correlation) 0.95 (95% CI: 0.88–0.98) and good for sagittal plane cervical ROM with ICC 0.90 (95% CI: 0.77–0.96). A repeated measures ANOVA determined that mean ROM recorded during the FRT differed significantly between assessment points (F(1.99, 41.83) = 19.88, P < 0.001). Bonferroni Post hoc tests revealed that both conscious Occlusion and Palate tongue position elicited a significant large reduction in ROM recorded during the FRT from baseline (p < 0.01). Despite this, one activation strategy did not influence ROM more than the other. An additional repeated measures ANOVA determined that mean sagittal cervical ROM did not significantly vary between assessment points (F(2, 42) = 8.18, P = 0.08). Conclusion: This current study provided further evidence for the influence of the temporomandibular region on upper cervical ROM. Results suggest that clinicians should focus on the natural mandible rest position when evaluating upper cervical mobility.